Network copolymers of acrylic and methacrylic acids: Hydrophilic ointment bases for wound-healing preparations - Tazhbaev, E. M.; Pak, R. N.; Akhmetova, S. B.; Burkeev, M. Zh.; Gulyaev, A. E.; Adekenov, S. M. (Springer US, 2007)
Investigations aimed at the development of a combined wound-healing preparation on a hydrophilic ointment base have been carried out. Copolymers of acrylic acid and its derivatives with a new divinyl monomer, β-vinyloxyethylamide of acrylic acid, are proposed as the bases. It is established that these ointment bases exhibit sufficiently high osmotic activity. Polymer-based complexes including the ethereal oil of smooth wormwood and the proteolytic enzyme protosubtilin showed pronounced antibacterial and wound-healing activity.